Acute myeloblastic leukaemia associated with solitary plasmacytoma of the ilium. Issue 734 (December 1986) - Maharaj, D.; Dolan, G.
Abstract : A 72 year old man developed acute myeloblastic leukaemia two years after he had been treated with local curative therapy and chemotherapy for a solitary plasma cytoma of the ilium.